2005
DOI: 10.2535/ofaj.82.25
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Variations of the Extensor Pollicis Brevis Tendon and Abductor Pollicis Longus Tendon

Abstract: Sufficient improvement in De Quervain disease, is not always archieved even by tenosynovectomy, and the reason for this appears to be anatomical variation in the first extensor compartment of the hand. In this study we examined the first extensor compartment of 159 hands of 80 human cadavers. Hiranuma and colleagues documented four anatomical types of first compartment, and in this study type A was observed in 76 (47.8%) of the 159 hands, type B in 49 (30.8%), and type C in 21 (13.2%). No type D compartments i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 1 publication
2
29
0
4
Order By: Relevance
“…We also observed that the frequencies of complete and incomplete septa were 44.4 and 55.5 %, respectively. Previous studies stated frequencies of a complete and incomplete septum as 23.2-53.5 % and 8.9-47 %, respectively [9,12,13,16,21]. Our results were coherent with the literature.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…We also observed that the frequencies of complete and incomplete septa were 44.4 and 55.5 %, respectively. Previous studies stated frequencies of a complete and incomplete septum as 23.2-53.5 % and 8.9-47 %, respectively [9,12,13,16,21]. Our results were coherent with the literature.…”
Section: Discussionsupporting
confidence: 95%
“…A limitation of our study was our relatively small sample size in regard to previous cadaveric studies [9,12,16,21]. A second limitation was that once we opened the extensor sheath, it was impossible for us to evaluate the inner morphometry of the 1stEC.…”
Section: Discussionmentioning
confidence: 89%
“…Many anatomical variations of the first dorsal compartment of the wrist and the tendons of the EPB and the APL have been reported. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] Reports have documented higher incidences of multiple APL tendons and an EPB subcompartment in patients with de Quervain's disease than in the general population, 1,2,[5][6][7]9,10,14 and the possible impact on the etiology and treatment of the disease has been discussed. 1,2,14 It has previously been noted 15 that the EPB is absent in 5% to 7% of individuals, which is consistent with the incidence of 6% of the wrists having no EPB in the de Quervain's group in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The APL is classically considered to be a thumb abductor and the EPB to be a metacarpophalangeal joint extensor, although their action may vary because there are many anatomical variations in this region. [1][2][3][4][5][6][7][8][9][10][11] The APL has more than 1 tendon slip in most cases, [1][2][3]6,7,9 and the EPB may be found in a separate subcompartment within the first dorsal compartment. 1,2,4 -7,9,10,12,13 The ability of the EPB to extend the thumb interphalangeal (IP) joint has been noted.…”
mentioning
confidence: 99%
“…Anatomical studies and clinical findings in the operative treatment of de Quervain's disease confirmed the high number of anatomical variations in the abductor pollicis longus and extensor pollicis brevis muscles [15]. The presence of these variations might lead to failure of treatment of de Quervain's disease even if tenosynovectomy was done [24].…”
Section: Introductionmentioning
confidence: 88%